Indications and Results for Ga-68 PSMA PET/CT in Patients with Biochemical Relapse of Prostate Cancer - Ivan Rogić; Tea Golubić; Margareta Dobrenić; Marijan Žuvić; Tea Šmitran; Nino Jukić; Dražen Huić (Acta Clinica Croatica)
In order to evaluate the diagnostic performance of 68Ga-PSMA PET-CT, we retrospectively analysed 100 patients with biochemically confirmed recurrence (BCR) of prostate cancer (PC). We compared positivity rates of PSMA PET scans with well-established disease indicators such as serum PSA levels, initial PSA (iPSA), PSAdt (PSA doubling time), elapsed time from prostatectomy, and Gleason score (GS). Of the 100 studies, 56 (56%) had lesions with pathological 68Ga-PSMA uptake. Positivity rate of PSMA PET studies was 50% (28/56) for PSA levels of 0.2-0.5 ng/mL, 47.83% (11/23) for PSA 0.51-1 ng/mL, 71.43% (10/14) for PSA 1.01-2 ng/mL, and 100% (7/7) for patients with PSA above 2.01 ng/mL. PSMA-PET/CT study positivity correlated with higher Gleason score (3+4 – 31.82%, 4+3 – 63.16%, 8 – 60%, and 9 – 85.71%). Local recurrence was found in 19.43% and lymph node metastases in 75% of studies with pathological tracer uptake, while bone metastases were found in 25% of PSMA-PET/CT positive studies. Regarding PSAdt, the PSMA-PET/ CT positivity rate was 66.67% (20/30) in cases with short PSAdt of less than 6 months, 57.14% (12/21) for PSAdt >6≤12 months, whereas only 23.53% (4/17) were positive in a group with very long PSAdt of >12 months. We have demonstrated that PSAdt may be considered the main positivity predictor of disease recurrence. Shorter PSAdt, even with low values of serum PSA, was linked with a higher positivity rate, while longer PSAdt was most often linked with negative scans. 68Ga-PSMA PET/CT is a sensitive PET method for the detection and localization of lesions in early biochemical recurrence of disease, even in cases with very low PSA serum values.